(untitled) (Bangladesh Journal of Psychiatry, 2020)
Sleep quality and well-being are interrelated. The objective of this study was to find this relationship between the well-being of persons with their quality of sleep and its correlates. It was a cross-sectional study conducted on respondents of 18 and above from September 2015 to October 2015. The study was done at Rangamati town, Kaptai Upazila of Rangamati district, three Upazila of Chittagong district, Dhaka city and Cox’s Bazar town in Bangladesh. A purposive sampling technique was used and the sample size was 109. The quality of sleep was assessed by the Pittsburgh Sleep Quality Index (PSQI) and the level of well-being was assessed by the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) among the respondents. The results showed that, among the 109 respondents, good sleepers were 53 (48.6%) and poor sleepers were 56 (51.4%). Regarding well-being level, the average was 89 (81.6%) and above-average was 20 (18.3%) among the respondents. Among good sleepers, 41 (77.3%) and poor sleepers 48 (85.7%) were found in the average level of well-being. Above average level of well-being was found 12 (22.6%) in good sleepers and 8 (14.3%) in poor sleepers. Well-being level was better among the good sleepers than poor sleepers but was not statistically significant (p>0.05). Here, the well-being level was better, but sleep quality was not satisfactory. Other factors which might influence the quality of sleep and well-being should also be considered. Bang J Psychiatry 2020; 34(1):14-17